ANALISIS KINERJA WEBSITE MENGGUNAKAN PENDEKATAN AUTOMATED SOFTWARE TESTING - I Gede Totok Suryawan; I Gede Dana Paramitha (LPPM Universitas Dhyana Pura, 2020)
ABSTRACTThis paper discusses the performance analysis of the STMIK STIKOM Indonesia website (www.stiki-indonesia.ac.id) using automated software testing. The software used is GTmetrix, Pingdom, and the Grander Website. Performance testing is based on website performance, no of requests, speed, load time, page size. The test results are given in the form of grades with scores in the form of numbers. These values are marked qualitatively with the letters A, B, C, D, E, and F, while the scores are marked quantitatively with numbers. In addition to the grade test results are also equipped with recommendations for improvement for each evaluation point. Performance testing is done by using an internet connection with download speed of 6.11 Mbps and 1.73 Mbps upload where the internet speed is tested using speedtest.net. The test results show that overall the STMIK STIKOM Indonesia website has a good performance, namely at level B with an average speed of 81.5%. While the page detail test results show that the average page load time is 7.88s and the total page size is 3.78MB, and the request count reaches 28. There are 7 recommendations that are recommended to optimize the STMIK STIKOM Indonesia website, namely by Optimizing Image, Leverage Browser Change , Inline Small CSS, Inline Small Javascript, Optimize the Order of Styles and Script, Sitemap Implementation, and Secure Socket Layer (SSL) Implementation.Keywords: Website, Website Performance, Automated Software Testing, Search Engine OptimizationABSTRAKPaper ini membahas tentang analisis kinerja website STMIK STIKOM Indonesia (www.stiki-indonesia.ac.id) menggunakan automated software testing. Adapun software yang digunakan yaitu GTmetrix, Pingdom, dan Website Grander. Pengujian kinerja didasarkan pada performa website, no of requests, speed, load time, page size. Hasil pengujian diberikan dalam bentuk grade dengan skor berupa angka. Nilai tersebut ditandai secara kualitatif dengan huruf A, B, C, D, E, dan F, sedangkan skornya ditandai secara kuantitatif dengan angka. Selain grade hasil pengujian juga dilengkapi dengan rekomendasi perbaikan untuk setiap poin evaluasi. Pengujian kinerja dilakukan dengan menggunakan koneksi internet dalam kecepatan download 6,11 Mbps dan upload 1,73Mbps dimana kecepatan internet tersebut ditest menggunakan speedtest.net. Hasil pengujian menunjukan bahwa secara keseluruhan website STMIK STIKOM Indonesia memiliki kinerja baik yaitu di level B dengan kecepatan rata-rata mencapai 81,5%. Sedangkan hasil pengujian page detail terlihat bahwa page load time rata-rata 7,88s dan total page size 3,78MB, serta request count mencapai 28. Ada 7 rekomendasi yang disarankan untuk mengoptimalkan website STMIK STIKOM Indonesia yaitu dengan melakukan Optimize Image, Leverage Browser Change, Inline Small CSS, Inline Small Javascript, Optimize the Order of Styles and Script, Implementasi Sitemap, dan Implementasi Secure Socket Layer (SSL).Kata kunci : Website, Kinerja Website, Automated Software Testing, Search Engine Optimization